2016
DOI: 10.1186/s13014-016-0703-x
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 depletion in combination with carbon ion exposure significantly reduces MMPs activity and overall increases TIMPs expression in cultured HeLa cells

Abstract: BackgroundHadron therapy is an innovative technique where cancer cells are precisely killed leaving surrounding healthy cells least affected by high linear energy transfer (LET) radiation like carbon ion beam. Anti-metastatic effect of carbon ion exposure attracts investigators into the field of hadron biology, although details remain poor. Poly(ADP-ribose) polymerase-1 (PARP-1) inhibitors are well-known radiosensitizer and several PARP-1 inhibitors are in clinical trial. Our previous studies showed that PARP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
0
21
0
Order By: Relevance
“…PARP-1 binds to SSBs and catalyzes the polymerization of ADP-ribose (PARylation), resulting in the production of polymers of ADP-ribose (PAR). We have reported that the combination of depletion of PARP-1 and C-ion exposure sensitizes HeLa cell and induces apoptosis to a greater extent than C-ion exposure alone [32].…”
Section: Introductionmentioning
confidence: 92%
“…PARP-1 binds to SSBs and catalyzes the polymerization of ADP-ribose (PARylation), resulting in the production of polymers of ADP-ribose (PAR). We have reported that the combination of depletion of PARP-1 and C-ion exposure sensitizes HeLa cell and induces apoptosis to a greater extent than C-ion exposure alone [32].…”
Section: Introductionmentioning
confidence: 92%
“…For carbon ion irradiation, multiple in vitro studies have shown that the use of a PARP inhibitor can sensitize cancer cells to carbon ion irradiation (Table 3) (97,98,212). Interestingly, some of these studies showed that PARP inhibition has a higher radiosensitizing effect in combination with carbon ion radiation compared to photon irradiation (97,98,101). Overall, combining particle radiation with PARP inhibition shows very promising results concerning radiosensitization.…”
Section: Inhibition Of Parpmentioning
confidence: 99%
“…Cells were maintained in Radiation Biology Laboratory at IUAC, New Delhi. The irradiation of cells was done using heavy ion irradiation facility ASPIRE, where the dosimetry is done using silicon surface barrier detectors [ 39 , 40 ]. We have used 12 C beam with 85MeV (equivalent to 7.08 MeV/nucleon) energy from the accelerator.…”
Section: Methodsmentioning
confidence: 99%